A Systematic Review of the Project Management Information Systems in Different Types of Construction Projects (Revista Galega de Economía)
Project management information systems (PMIS) are software instruments that help managers track projects from design to execution. A PMIS is primarily developed to help project management. Therefore, some issues worth considering are how much the available systems adopt project management methods outlined in project management theory, how much software applications make seeking assistance possible at individual phases of the project life cycle, and if this scope is sufficient. In this study, different types of PMIS, such as web-based and software applications were investigated. Then, the implementation of PMIS, its factors, and its effect on projects such as construction, manufacturing, IT, R&D, and finance were examined. Lastly, future potential paths for other researchers were discussed. Projects can  be managed, planned, organised, staffed, monitored, controlled, and evaluated through the project management system  can ensure that projects are managed and conducted professionally